School, society and culture - the relevance of heritage school - Machado dos Santos, Adelcio (Seven Editora, 2023)
Man, an ontologically social being, shows the necessity of knowing and building comprehension of the methods and processes which are fundamental to the organization and the viability of the act of living. Knowledge is a product of conscious activity of thinking that determines the social nature of human beings and makes their history and culture. But man is not born to live together in society. He must be raised to learn how to live in society. It is necessary that he is raised to learn how to live with his history and the making of it. To do so, different institutions have been created inside societies, whose primary function is to control certain sectors of the beh avior of individuals through the transmission of patterns of behaviour and culture. One of the most social formations which interacts directly with society, influênciang and allowing themselves to be influenced, is the educational organization. Through it, man learns how to live socially, assimilating the culture, the pattern of behaviour, the knowledge produced. Education also exerts social control over human behaviour. It is evident, thus, the deep interaction that exists between education and society. The educational process must engage the social role, mediating sociability and preparing the man for the application of knowledge through the exercise of the transforming activity of nature. In this context, it is necessary the school to act as guardian of the historical development, through the "Heritage Education". DOI: https://doi.org/10.56238/tfisdwv1-104